Transcutaneous Electric Nerve Stimulator Induced Inappropriate ICD Shock - Naeem Al-Shoaibi (Journal of King Abdulaziz University: Medical Sciences, 2023)
Inappropriate shock delivered by implantable cardioverter defibrillators due to electromagnetic interference is a well-known phenomenon. This case report is about a new source of interference from a transcutaneous electronic nerve stimulation unit. Although the artifact from transcutaneous electronic nerve stimulation and interference with appropriate function of cardiac pacemakers is well documented, adverse interaction with implantable cardioverter defibrillators has rarely been reported. This case present a patient in whom a transcutaneous electrical nerve stimulation (a unit created an electrical artifact that was interpreted by a trans-venous implantable cardioverter defibrillators as ventricular fibrillation), led to the delivery of inappropriate therapy. Transcutaneous electrical nerve stimulation units should be used with caution in patients with implantable cardioverter defibrillators.